Impact of the Warning through Local Image Character and Language Text for Smokers’ Awareness of Health Risks and Interest in Quitting Smoking - Afzaal Ali; Mehkar Sherwani; Adnan Ali (Archives of Current Research International, 2016)
Aims: This research attempts to empirically evaluate the local image character and language text concept to better explain the stages of change model to predict the behavioral change in smokers. Study Design: The current research study is descriptive, applied and deductive in nature. Moreover, this is a cross-sectional research study as the data was collected once from the respondents under study using a structured questionnaire. Methodology: As smoking prevalence is high among young people, the authors included 219 young male smokers by using purposive sampling technique. This study was conducted on a volunteer basis, 81 out of 300 committed respondents’ refused to participate in the end. Smokers from two Pakistani cities viewed three health warnings on cigarette packets, which included (text-only warning, adopted text-plus graphical warning, and local text-plus graphical warning). Data were collected in April, 2014 and analyzed also in 2014. Results: The findings suggest that there are significant differences in the effectiveness of three types of anti-smoking health related warnings. Text-plus graphical warnings cause smokers more than text-only warnings to pay more attention on warning, lead smokers having higher levels of fear, make them to stop from having a cigarette, and develop more motivation to quit finally. Most importantly, the current study adds to the evidence that warning label with local image character and language text is more effective than text-only warning, and warning label with adopted image character and language text. Conclusion: The authors suggest that the health policy making institutions in other developing countries may use graphical warnings on cigarette packets with local character images and language text. According to the results of study, this policy can be more effective to get smokers’ attention, raise awareness and educate smokers about the health hazards of smoking.